Compositional Analysis of Bukidnon State University Scholarship Grantees - Arlene R Pagaura; Lora E Añar (XXXXXXXX, 2023)
ABSTRACT: The study determined the compositional analysis of scholarship grantees in terms of personal, academic, social and interest profiles. The participants were the 574 grantees from the different colleges of Bukidnon State University. The data were obtained from the Office of Students Services and complemented with a questionnaire. This is a descriptive research. Frequency, percentage and discriminant analysis were utilized in analyzing data. The findings revealed that there are sixteen kinds of scholarships of the university. These are offered to students who belong to cultural communities, dean’s lists, outstanding members of performing arts, emancipated children of regular faculty members and staff, poor but deserving. As to parents’ occupation, it was farmer-housewife tandem with a monthly income below fifteen thousand. As to academic profile, Bachelor of Science in Business Administration had the most grantees. Most of the grantees were members of Young Educator’s Club, College Disaster Management Unit (CDMU), and other religious organizations. Majority of the grantees were engage in dancing, playing musical instruments and reading books. The parents’ monthly income is the strongest predictor in availing the scholarship program.Keywords:  Academic and Social Profile, Interest Profile, Personal Characteristics, Scholarship Programs